Pola Pengasuhan Positif Orangtua Pada Anak Usia Dini Selama Belajar Dari Rumah di masa Pandemi Covid-19 - Mila Karmila; Rieyani Okta Sumbawa (Institut Agama Islam Negeri Madura, 2021)
When the Covid-19 virus entered Indonesian territory, the Indonesian government immediately followed up on the case by changing the education system in Indonesia into distance learning or commonly called BDR. The research methodology used is literature study as material to review seven to ten relevant studies regarding positive parenting patterns of parents while studying from home during the COVID-19 pandemic. Parents are expected to provide positive parenting, which is expected to be better to assist in the smooth learning of children at home during the Covid-19 pandemic, which is very important. Are the results such as assisting children in doing school assignments, supporting and facilitating children in learning, supporting and facilitating children in learning, establishing good communication between families, choosing the right parenting style, and respecting children's opinions, making rules at home. The role of parents is very influential in assisting children to learn from home.